Entangled Ekphrastics: Proliferating Modes of (Post) Qualitative Inquiry Through Liminality and Research-Creation - Riley, Kathryn; Goode, Gretchen; Varga, Bretton A.; Eaton, Paul William; Salvador-García, Celina; Byers, Christie C. (Reconceptualizing Educational Research Methodology, 2025)
In this article, we articulate a research-creation process called entangled ekphrastics as an emergent response to -isms: racism, capitalism, colonialism, heteropatriarchalism, speciesism, and nationalism. Our collective gathered virtually, engaged with artwork, and co-created (entangled) poems. This research-creation process generated profound appreciation for disrupting conventions of traditional qualitative inquiry, pushing the boundaries of activism and artivism in the present moment. We wonder about how responding to the present through entangled ekphrastics moves us toward theoretical liminality, hospicing the crises of the present, and midwifing a future together.